(untitled) (Journal of Educational Sciences, 2023)
The PISA International Student Assessment Program (Program for International Student Assessment) is one of the most authoritative studies in the field of school education quality. The relevance of the article is due to the factors influencing the achievements of Kazakhstani students in the PISA-2018 international study. This article uses factor-centric research design, in which the main purpose is to calculate the direction and size of one or more variables of interest. The main directions and the idea of scientific research are characterized by the results of the PISA study, which broadcast a large number of factors affecting the results of schoolchildren, which can be divided into geographical, school, family-biographical and socio-economic. The scientific and practical significance of the work lies in the fact that, based on a literary review, an index of socio-cultural and economic status, a resistance index, etc. were selected for modeling at the group level. The research methodology includes multilevel regression analysis, complex sampling design, statistical analysis, multilevel linear regression, calculations of variance of random effects, the possibility of adding fixed effects at the group level. As the main results and analysis, as well as the conclusions of the research work, we can cite models for mathematical, reading and natural science literacy of 15-year-olds, in which only a random constant is calculated, without including predictors at the individual and group levels. The value of the conducted research lies in the first attempt to collect the main factors explaining the results of Kazakhstani schoolchildren in such areas of the PISA-2018 study as mathematics, reading and natural science at the individual, school and regional levels. The practical significance of the results of the work is considered in the analysis of persistent factors of inequality over 10-14 years of development of the education system in the Republic of Kazakhstan. Further study of the language difference and the influence of the generally accepted typology of schools on the test results is recommended. Key words: school education quality, statistical analysis, plausible values, complex sampling design.